2005
DOI: 10.1146/annurev.publhealth.26.021304.144437
|View full text |Cite
|
Sign up to set email alerts
|

DECLINING RATES OF PHYSICAL ACTIVITY IN THE UNITED STATES: What Are the Contributors?

Abstract: This review describes current patterns and long-term trends (up to 50 years when possible) related to (a) physical activity, (b) employment and occupation, (c) travel behavior, (d) land use, and (e) related behaviors (e.g., television watching). On the basis of available data, the following trends were observed according to type of physical activity: relatively stable or slightly increasing levels of leisure-time physical activity, declining work-related activity, declining transportation activity, declining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
551
2
32

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 786 publications
(615 citation statements)
references
References 36 publications
19
551
2
32
Order By: Relevance
“…1 Just half of American adults reported meeting 2008 Department of Health and Human Services (HHS) weekly recommendations of 75 min of vigorous-intensity physical activity or 150 min of moderate-intensity physical activity. 2,3 In New York City (NYC), 60 % of adults reported meeting those recommendations in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…1 Just half of American adults reported meeting 2008 Department of Health and Human Services (HHS) weekly recommendations of 75 min of vigorous-intensity physical activity or 150 min of moderate-intensity physical activity. 2,3 In New York City (NYC), 60 % of adults reported meeting those recommendations in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, evidence has suggested that the primary problem lies not with increased energy intake [15][16][17][18] but with reduced expenditure, that is reduced physical activity. 15,[19][20][21] With respect to dietary intake, surveys between the 1970s and 2000s do not indicate that total energy consumption has increased. 15,16 Moreover, fat consumption seems to have decreased.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one recent multiple health behavior change intervention focused on nutrition, gender was not associated with behavior change [11]. An important aspect of addressing the disparities in healthy lifestyle behaviors by occupational class [2, [4][5][6][7][8] is identifying appropriate intervention strategies for worksites that employ substantial proportions of men.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple modifiable health behaviors, such as diet and physical activity, are risk factors for these chronic diseases [2,3]. Disparities exist across US occupational classes and socioeconomic levels for meeting recommended goals for diet and physical activity; for example, blue-collar workers and people with lower socioeconomic position exhibit higher risk [2, [4][5][6][7][8]. While disparities in health behaviors across occupational class are well documented for discrete health behaviors [8], a few studies have also suggested that there may be disparities in clustering of health behaviors among people of different occupational classes and socioeconomic and education levels [9,10].…”
Section: Introductionmentioning
confidence: 99%